Bio‐Inspired Antibacterial Hydrogel Adhesives with High Adhesion Strength. Issue 17 (17th June 2022) - Liang, Lei; Qin, Zhihui; Dong, Xiaoru; He, Shaoshuai; Yao, Mengmeng; Yu, Qingyu; Yu, Chaojie; Liu, Min; Guo, Bingyan; Zhang, Hong; Yao, Fanglian; Li, Junjie
Abstract: Traditional adhesives such as cyanoacrylate glue are mostly solvent‐based. They are facing the problem of insufficient adhesion to some substrates, and also from the drawback of volatilization and release of small organic molecules in the process of usage. Therefore, a novel adhesive with non‐irritating, high adhesive strength, and antibacterial properties is highly required. In this study, a full physically crosslinked zwitterionic poly(betaine sulfonate methacrylate) (PSBMA) hydrogel is proposed. The physical crosslinking interactions endow the hydrogel with good self‐healing properties. Furthermore, the pure physical crosslinking hydrogel can form PSBMA powder adhesive after lyophilization and return to the hydrogel state after hydration. The mechanical properties of PSBMA adhesive can be modulated via adjusting the solid content and initiator dosage. Following the cure process similar to that of snail mucus or insect exoskeletons in nature, the adhesion of the PSBMA adhesive is improved at least 100 times than its wet state. In addition, the PSBMA adhesive is easy to be removed due to the dissociation of cross‐linked structures in saltwater environments. Moreover, PSBMA adhesive with antifouling properties can effectively prevent the adhesion of proteins and bacteria, which shows potential applications in the assembly of medical devices. Abstract : In this work, a novel non‐irritating, high adhesive strength, and antibacterial adhesive is prepared. The electrostatic interactions contribute to the formation of physical hydrogel and the excellent hydrogel‐powder‐hydrogel recycle property. Also due to the zwitterionic groups in the polymers and bio‐inspired cure process, the hydrogel adhesive achieves antifouling properties and strong bonding interaction.